Respuesta :

Answer:

[tex]-2x[/tex]

Step-by-step explanation:

We are given the function [tex]g(x)=5-x^2[/tex] and the expression[tex]\lim_{x \to 0}  \frac{g(x+h)-g(x)}{h}[/tex]

First, we must substitute in x+h into g(x) and substitute in g(x) into the expression

[tex]\lim_{h \to 0}\frac{5-(x+h)^2-(5-x^2)}{h} \\[/tex]

Next, we can simplify by multiplying out the exponents and then combine like terms

[tex]\lim_{h \to 0}\frac{5-(x+h)^2-(5-x^2)}{h} \\\\\lim_{h \to 0}\frac{5-x^2-2xh-h^2-5+x^2}{h} \\\\\lim_{h \to 0}\frac{-2xh-h^2}{h} \\[/tex]

Next, we can divide the numerator by the denominator to get

[tex]\lim_{h \to 0}\frac{-2xh-h^2}{h}\\\\\lim_{h \to 0} -2x-h[/tex]

Lastly, we can substitute in 0 for h

[tex]-2x-0\\\\-2x[/tex]

ACCESS MORE